800 Years of Making: Early Medieval Craftworking and an 8th-Century Decline in Ireland. - Hannah, Emma (Medieval Archaeology, 2021)
METHODOLOGICAL ADVANCES IN STATISTICAL MODELLING of chronological data have enabled fresh perspectives of the past to be gained from the analysis of large numbers of radiocarbon (C) dates. A new analysis of radiocarbon dates associated with craftworking activities — handicrafts like antler-working or wood-working and metalworking technologies — from Irish sites of early medieval date is presented using a bootstrapped kernel density estimation (KDE) method. These models are used to assess whether the arrival of urbanism to Ireland in the 10th century brought about a major change to craftworking traditions, and to build a new and nuanced understanding of long-term trends at both secular and ecclesiastical sites of the period. These are shown to have differed, especially in the 8th century, at a crucial point in time. The findings add to the emerging narrative of demographic 'decline' from similar data-driven investigations of Ireland's early medieval past, which pinpoint the beginning of the 8th century as a seminal moment of change. Crucially, however, they also reveal a more complex pattern of change involving a combination of processes, independent of urban development, but related to demographics, socio-economic re-organisation, changing settlement patterns, and the influence of the Church.